Rancang Bangun Alat Percobaan Ayunan Bandul Sederhana Berbasis Arduino - Irsal Herijul Sinaga; Moranain Mungkin; Muhammad Fadlan Siregar (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
In general, we are certainly no stranger to seeing a tool called a simple pendulum swing for measuring the acceleration of gravity which is often shown during basic physics practicum courses. A simple pendulum swing with a manual measurement pattern is a physics practicum teaching aid that aims to measure the value of the acceleration of gravity with the form of a series of tools in the form of a small object, namely a solid ball and hung on a rope whose mass can be neglected. Then the other end of the rope is hung on a fixed hanger, after which if the pendulum is given a small deviation and then released, the pendulum will oscillate (vibrate) between two points, for example points A and B, with a fixed period T. Where the variables measured are the period (T), the mass of the pendulum (m), the angle deviation (O) and the length of the string (L) which will then be processed into an equation to find the value of the acceleration due to gravity. While the simple pendulum swing device with a digital pattern is a teaching aid for physics practicum whose purpose is also the same, namely to measure the value of the acceleration of gravity with the form of a series of tools that are also almost the same but the difference is the addition of intelligent electronic devices, namely the Arduino module as a control system and proximity sensors and push buttons. button as input device. The description related to the function of the electronic device for measuring the time variable of a pendulum when swinging is carried out using a capacitive proximity sensor with an Arduino internal timer facility. While the manual pattern usually uses a stopwatch.